1998
DOI: 10.1046/j.1365-2796.1998.00299.x
|View full text |Cite
|
Sign up to set email alerts
|

Exercise‐induced aortic flow parameters in early postmenopausal women and middle‐aged men

Abstract: Objective. Exercise Doppler echocardiography has been recognised as an accurate method for the assessment of left ventricular function in patients with coronary artery disease. Gender differences in aortic flow parameters during exercise have not been well established. The aims of this study were to compare basal ejection Doppler indexes in healthy early postmenopausal women with those of men, and to assess the effects of both isometric and dynamic exercises on these parameters. Design. Intergroup comparison b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Female gender was associated directly with augmented aortic flow velocity in our study. The same data were reported previously [33]. Women have been shown to have proportionally smaller heart and aorta than men and higher cardiac outputs because of the lower oxygen-carrying capacity of their blood (lower hemoglobin levels as well as lower peripheral oxygen extraction).…”
Section: Discussionsupporting
confidence: 85%
“…Female gender was associated directly with augmented aortic flow velocity in our study. The same data were reported previously [33]. Women have been shown to have proportionally smaller heart and aorta than men and higher cardiac outputs because of the lower oxygen-carrying capacity of their blood (lower hemoglobin levels as well as lower peripheral oxygen extraction).…”
Section: Discussionsupporting
confidence: 85%
“…10 Although biologic factors have been examined to elucidate mechanisms by which atherosclerosis develops more slowly in females, and in some cases less often than in males, hemodynamic differences between men and women have not been well documented. Lev et al 11 compared left ventricular function of postmenopausal women and middle-aged men with Doppler ultrasound scan, although only at rest. Gender differences in abdominal aortic flow and wall shear stress have not been previously reported at all.…”
mentioning
confidence: 99%
“…Compared to dynamic stress testing, pharmacological stress showed lower mean change of HR (21.29 bpm, 95% CI −39.53 to −3.04), lower change of SV (15 ml, 95% CI −28.46 to −1.54; reported in one study) and lower change of CO (5.22 l/min, 95% CI −9.63 to −0.81). Two studies with 3 cohorts reported differences between isometric and dynamic exercise (54, 55). Compared to dynamic exercise, isometric exercise showed lower mean change of HR (35.94 bpm, 95% CI −64.31 to −7.57), higher change of SV (2 ml, 95% CI −53.31 to 57.31), lower change of CO (8.20 l/min, 95% CI −12.85 to −3.55) and higher change of SET (30.56 ms, 95% CI −36.07 to 97.16).…”
Section: Resultsmentioning
confidence: 99%